FREINET’S CONCEPT OF TEACHERS AND THEORY OF TEACHING - Nowak-Fabrykowski, Krystyna (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1992)
The aim of this paper is to present Celestin Freinet’s concept of a teacher. His theory which focuses on the teacher’s personality and practice is illustrated through teaching practice and psychological theory. To understand Freinet’s theory, it is necessary to analyze his psychological concepts, which were closely related to his teaching methods. His principal idea is that school should reinforce the positive traits of a child’s personality by giving the child possibilities for creative work. This can be achieved by using new teaching techniques such as "slip problems," a school journal, free text, printing text by students, and school-to-school correspondence. As complementary material the author presents a brief history of the Freinet Movement in France. RÉSUMÉ Cet article a pour objet de présenter le concept de l’enseignement selon Célestin Freinet. Sa théorie, illustrée par la pratique de l’enseignement et la théorie psychologique, s’articule autour de la personnalité et des méthodes du professeur. Pour bien comprendre la théorie de Freinet, il faut analyser ses concepts psychologiques qui ont un rapport étroit avec ses méthodes d’enseignement. L’idée maîtresse est que l’école doit renforcer les traits positifs de la personnalité d’un enfant en lui donnant la possibilité de laisser libre cours à son imagination. Pour ce faire, l’enseignante peut recourir à de nouvelles techniques pédagogiques comme les méthodes actives, les journaux scolaires, le texte libre ou l’imprimerie à l’école et la correspondance interscolaire. Comme matériels complémentaires, l’auteur présente un bref historique du mouvement Freinet en France.